Separating the impact of oxygen and water on the long-term stability of n-channel perylene diimide thin-film transistors - Zschieschang, Ute; Amsharov, Konstantin; Jansen, Martin; Kern, Klaus; Klauk, Hagen; Weitz, R. Thomas (Organic Electronics, 2015)
Abstract A detailed understanding for the mechanisms that control degradation of the electrical performance of organic thin-film transistors (TFTs) during exposure to various environments, such as oxygen and humidity, is still developing. This is particularly true for n-channel organic TFTs. Here we present an investigation of the long-term stability of n-channel TFTs based on the small-molecule organic semiconductor N,N′-bis(2,2,3,3,4,4,4-heptafluorobutyl-1,7-dicyano-perylene-(3,4:9,10)-tetracarboxylic diimide (PDI-FCN2) during storage in dry nitrogen, dry air, wet nitrogen and ambient air. By monitoring the electrical characteristics of the TFTs over a period of six weeks, we are able to show that the degradation of the electrical parameters (charge-carrier mobility and the simultaneous shift of the threshold voltage) is caused by two distinct mechanisms with different time constants. Exposure to oxygen or nitrogen (in the absence of humidity) causes the carrier mobility to drop by a factor of two and the threshold voltage to shift towards more positive values within 20 days, possibly due to a slight rearrangement of the conjugated molecules within the semiconductor layer. Storing the TFTs in saturated water vapor or in ambient air causes the threshold voltage and the carrier mobility to change much more rapidly, within just one day. The observed degradation in ambient air can be explained by an electrochemical instability of the radical anion of the organic semiconductor.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Ambient stability; n-Channel; Organic transistor; Perylene diimide